Identification and Prioritization of "Black Spots" without Using Accident Information. (15th March 2017) - Keymanesh, Mahmoudreza; Ziari, Hasan; Roudini, Samira; Nasrollahtabar Ahangar, Ali
Abstract : It is attempted to identify and prioritize the accident prone points (black spots) in "Iraanshahr-Sarbaaz-Chabahar" road located in Baluchistan, Iran, without no use of accident data but rather using Analytic Hierarchy Process (AHP), which is the enhanced procedure of road safety audit technique. First, by surveying the whole route, all factors that could influence accidents in this road were specified; then the route was divided into eight sections; this division was performed based on the uniformity and homogeny of each section in terms of geometric design and regional conditions. In each section, potentially hazardous locations were identified and some questionnaires were prepared, which were filled by 5 road traffic experts familiar with the route; then the collected data were analyzed by Analytical Hierarchy Process (AHP) using Expert Choice Software and the black spots were identified and prioritized. Finally, these black spots were compared with the black spots that had been obtained by traffic police based on accident data.